2019
DOI: 10.1097/md.0000000000015395
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian metastasis from breast cancer in three Chinese females

Abstract: Rationale:The biological behavior and clinical features of ovarian metastasis from breast cancer remain unclear; diagnosis and treatment of this condition are challenging.Patient concerns:We reported three cases of ovarian metastasis from breast cancer in Chinese women aged 44, 46, and 30 years. The prognosis was different in all three patients; however, no symptoms of ovarian metastasis were observed.Diagnosis:All three premenopausal patients were diagnosed with hormone receptor-positive breast cancer and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Though, ovarian metastasis is often seen in patients with invasive ductal carcinoma owing to a higher frequency of invasive ductal carcinoma. However, the metastatic tendency of invasive lobular carcinoma to the ovaries is three times greater [ 4 ]. On the contrary, Peters et al found that there are no significant differences in histological subtype between the cases and matched controls among young breast cancer patients [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though, ovarian metastasis is often seen in patients with invasive ductal carcinoma owing to a higher frequency of invasive ductal carcinoma. However, the metastatic tendency of invasive lobular carcinoma to the ovaries is three times greater [ 4 ]. On the contrary, Peters et al found that there are no significant differences in histological subtype between the cases and matched controls among young breast cancer patients [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most important step in the management of ovarian metastasis from breast cancer is surgery as it also helps in further diagnosis and staging. For a suspicious ovarian mass in breast cancer patients, a simple laparoscopic oophorectomy can help pathological diagnosis, metastatic tumor removal, and therapeutic castration [ 4 ]. However, high-risk women should be offered prophylactic oophorectomy and the need to possibly undergo a staging procedure if indicated should be well explained to those patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of higher rates of IC-NST among all morphological subtypes of breast carcinomas, there are more IC-NSTs encountered in ovarian metastases from breast cancer. Other disease criteria associated with ovarian metastases include ER-positive disease, node-positive disease, inflammatory cancer, large tumour size, and high histological grade [7]. The proliferation index Ki-67 is used as a prognostic and predictive tool in early breast cancer management [8].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Ki-67 higher than 15% is associated with a higher incidence of metastasis and recurrence; however, this is not specific to ovarian metastasis [9]. Ovarian metastases from primary breast cancer are repeatedly asymptomatic and often diagnosed as an incidental finding during follow-up imaging or after therapeutic oophorectomy; moreover, they commonly manifest as bilateral pathology [7]. Breast cancer metastases to the ovaries seldom occur as an isolated lesion.…”
Section: Discussionmentioning
confidence: 99%